A new approach designed for improving flame retardancy of intumescent polypropylene via continuous extrusion with supercritical CO2. Issue 113 (28th November 2016) - Huang, Pengke; Pang, Yongyan; Zhang, Lihua; Wu, Fei; Zhang, Shuhai; Zheng, Wenge
Abstract : scCO2 -aided IFR dispersion of PP/IFR composites and their improved flame retardancy. Abstract : The objective of this study was to explore a new approach to enhance the flame retardancy of polypropylene/intumescent flame retardant (PP/IFR) composites through improving IFR dispersion via continuous extrusion with supercritical carbon dioxide (scCO2 ) as the processing medium. The IFR used in this study consisted of ammonium polyphosphate (APP) and pentaerythritol (PER) at a weight ratio of 3 : 1. Scanning electron microscopy (SEM) was applied to study the dispersion of IFR in the PP composites prepared in the presence of different contents of scCO2 . Thermogravimetric analysis (TGA) was carried out to study the effect of IFR dispersion on the thermal stability and the yield of char residues of the PP composites. A plastic smoke generation tester was applied to study the specific optical density under a thermal irradiance. SEM was then used to study the morphologies of the intumescent char formed after the smoke testing. Limiting oxygen index (LOI) and vertical burning test (UL-94) ratings were evaluated to study the effect of IFR dispersion on the flame retardancy of the PP composites. It was found that scCO2 as the processing medium could significantly improve IFR dispersion and thus increase the efficiency of the flame retardant and enhance the flame retardancy of the PP composites. This new approach could allow PP composites to pass the UL-94 V-0 rating at a lower IFR content. Possible mechanisms were proposed for the scCO2 -aided IFR dispersion and the improved flame retardancy of the PP composites.